2023
DOI: 10.1007/s00259-023-06144-0
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast activation protein-targeted radionuclide therapy: background, opportunities, and challenges of first (pre)clinical studies

Abstract: Introduction Fibroblast activation protein (FAP) is highly overexpressed in stromal tissue of various cancers. While FAP has been recognized as a potential diagnostic or therapeutic cancer target for decades, the surge of radiolabeled FAP-targeting molecules has the potential to revolutionize its perspective. It is presently hypothesized that FAP targeted radioligand therapy (TRT) may become a novel treatment for various types of cancer. To date, several preclinical and case series have been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 54 publications
0
12
0
2
Order By: Relevance
“…However, the sponsor ceased further exploration of the drug because of a change in priorities in the portfolio ( ClinicalTrials.gov, ID: NCT03386721 ). Nonetheless, several active trials test the use of FAP to direct imaging agents ( Chandekar et al, 2023 ) and radiotheranostics ( Privé et al, 2023 ) to the tumors with fibroblast-rich stroma.…”
Section: Therapeutic Targeting Of Cancer-associated Fibroblastsmentioning
confidence: 99%
“…However, the sponsor ceased further exploration of the drug because of a change in priorities in the portfolio ( ClinicalTrials.gov, ID: NCT03386721 ). Nonetheless, several active trials test the use of FAP to direct imaging agents ( Chandekar et al, 2023 ) and radiotheranostics ( Privé et al, 2023 ) to the tumors with fibroblast-rich stroma.…”
Section: Therapeutic Targeting Of Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Another antibody, S5, exhibited expression patterns similar to mAbF19 but had limited in vivo expression [ 92 ]. It became evident that the fibroblasts surrounding tumor cells offer effective targets for cancer immunolocalization or immunotherapy, owing to their recognition by mAbF19 [ 129 , 130 , 131 ].…”
Section: Antibody-based Radiopharmaceuticals Targeting Fapmentioning
confidence: 99%
“…3-6 177 Lu-FAP-2286 promises to be an effective radiopharmaceutical for long retention and high uptake with acceptable adverse effects. 3,7,8 Previous study has reported the absorbed doses of 177 Lu-FAP-2286 for the whole body. 8 Our case shows the efficacy of 177 Lu-FAP-2286 for the treatment of metastatic bladder cancer, but there are still further studies needed.…”
Section: Figurementioning
confidence: 99%
“…FAP-targeting radionuclide therapy has been applied in refractory tumors of various types 3–6 . 177 Lu-FAP-2286 promises to be an effective radiopharmaceutical for long retention and high uptake with acceptable adverse effects 3,7,8 . Previous study has reported the absorbed doses of 177 Lu-FAP-2286 for the whole body 8 .…”
mentioning
confidence: 99%